Implementasi Model Literasi Informasi Pathways To Knowledge Dalam Strategi Promosi Lapak Baca Himpunan Mahasiswa Program Studi Ilmu Perpustakaan dan Informasi Islam (HMPS IPII) UIN SATU Tulungagung Periode 2023 - Farikha, Salma; Bela, Salsa (Ilmu Informasi Perpustakaan dan Kearsipan, 2023)
In this era of all-technology, there needs to be real awareness and movement within each individual to increase interest in literacy, especially among children. The 2023 Islamic Library and Information Science Study Program Student Association management has contributed to helping the government increase children's interest in reading by holding reading stalls in Tulungagung's Aloon-Aloon park. This study discusses the application of the Pathways to Knowledge method as a strategy for promoting reading stalls activities to the public. This article uses field research methods(field research) with a descriptive qualitative research approach. Based on the results of the researchers' observations, unknowingly the reading stall committee has implemented the Pathways to Knowledge literacy model in promoting its activities in the community. There are obstacles faced by the reading stalls committee, namely at the stage appreciation and level pra search often failed to persuade the target to come to the reading booth stand.